Postoperative platelet function is associated with severe bleeding in ticagrelor-treated patients. (22nd December 2018) - Björklund, Erik; Hansson, Emma C; Romlin, Birgitta S; Jeppsson, Anders; Malm, Carl Johan
Abstract: OBJECTIVES: Preoperative testing of platelet function predicts bleeding risk in cardiac surgery patients treated with dual antiplatelet therapy, but the value of postoperative platelet function testing, reflecting both preoperative antiplatelet therapy and perioperative changes in platelet function, has not been evaluated. METHODS: Seventy-four patients with acute coronary syndrome treated with acetylsalicylic acid and ticagrelor within 5 days before cardiac surgery were included in a prospective observational study. Platelet aggregation induced by adenosine diphosphate, arachidonic acid and thrombin receptor-activating peptide was assessed with multiple electrode impedance aggregometry immediately before surgery and 2 h after weaning off cardiopulmonary bypass. Receiver operating characteristic curves were used to determine any association between platelet aggregation and severe bleeding according to the universal definition of perioperative bleeding in adult cardiac surgery. RESULTS: Severe bleeding occurred in 25 of 74 patients (34%). Preoperative and postoperative adenosine diphosphate-induced platelet aggregations were associated with bleeding, with comparable areas under the receiver operating characteristic curve [0.77 (95% confidence interval 0.65–0.89) vs 0.75 (0.62–0.87)]. Postoperative arachidonic acid- and thrombin receptor-activating peptide-induced aggregation had markedly smaller areas under the curve. There were significant correlations between preoperative and postoperative platelet aggregation induced by adenosine diphosphate ( r 2  = 0.77, P  <  0.001), arachidonic acid ( r 2  = 0.24, P   <  0.001) and thrombin receptor-activating peptide ( r 2  = 0.21, P   < 0.001) but with large interindividual variations. CONCLUSIONS: Poor postoperative platelet function was associated with severe bleeding, with accuracy comparable to that of preoperative platelet function. There was a correlation between preoperative and postoperative platelet function, but the predictability in an individual patient was limited.